Pelatihan Packaging Produk Collection Fashion bagi Ibu-Ibu PKK RW 4 Binaan UKM Yuliart Collection Fashion Art and Painting Kel. Dukuh Sutorejo – Kec. Mulyorejo Kota Surabaya - Hwihanus Hwihanus; Sri Rahayuningsih; Dyah Rini Prihastuty (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2025)
Product packaging training is a crucial effort to empower the community, especially the PKK mothers in RW 4, Dukuh Sutorejo Village. This training aims to enhance participants' skills and knowledge in packaging fashion products to make them more attractive and increase their market value. The training focuses on creative packaging techniques tailored for fashion products produced by the UKM Yuliart Collection Fashion Art and Painting. The methods used include theoretical instruction and hands-on practice with a participatory approach. The results indicate a significant improvement in the participants’ understanding and ability to create appealing and functional product packaging. Consequently, this training is expected to improve the competitiveness of UKM products in local markets and strengthen the economic welfare of the participant families.